2011
DOI: 10.1007/s00415-011-5913-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects in myasthenic patients treated by plasmapheresis

Abstract: Knowledge about the postintervention psychosocial status of myasthenia gravis (MG) is limited and based on questionnaire studies. In this study, the effects of improvement in muscle strength with plasmapheresis treatment on both quality of life (QoL) and psychological status of MG patients were studied. Between January 2008 and December 2009, 29 MG patients were enrolled to receive one course of plasmapheresis treatment. Differences in baseline and posttherapy clinical, laboratory, and psychosocial measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…Psychosocial tests showed significant pre-and posttherapy differences in illness identity and disability. Patients especially were achieving immediate improvement of myasthenic symptoms but emotional status and HRQOL did not differ significantly after intervention [24]. Our observations were similarly.…”
Section: Discussionsupporting
confidence: 75%
“…Psychosocial tests showed significant pre-and posttherapy differences in illness identity and disability. Patients especially were achieving immediate improvement of myasthenic symptoms but emotional status and HRQOL did not differ significantly after intervention [24]. Our observations were similarly.…”
Section: Discussionsupporting
confidence: 75%
“…The direct impact of autoimmunity against the neuromuscular junction on cognition, mental fatigue and depression is controversial [39][40][41]. There is evidence to suggest mood and cognition may be independent of severity of symptoms, as seen in absence of improvement in mood despite abated symptoms after plasmapheresis [42].…”
Section: Discussionmentioning
confidence: 98%
“…Researchers have postulated that affective disturbances in MG may arise in response to the physical limitations imposed by muscle weakness and consequently may be reduced by alleviating somatic symptoms [14,25,26]. However, a study by Chen et al revealed that while plasmapheresis effectively cleared 56% of the pathogenic antibodies, correlating with a 46% reduction in MG score, as an indicator of decreased weakness, plasmapheresis failed to reduce rates of depression and anxiety [26]. Furthermore, Mean Mental Components of HRQoL remained low post-plasmapheresis, despite improved physical function and strength [26].…”
Section: Effects Of Mg Treatment On Moodmentioning
confidence: 99%